2014
DOI: 10.3109/14992027.2014.938194
|View full text |Cite
|
Sign up to set email alerts
|

Abstracts of the Fourth Joint Annual Conference, Experimental and Clinical Short Papers Meetings of the British Society of Audiology

Abstract: 1997 . Response properties of neurons in the inferior colliculus of the monaurally deafened ferret to acoustic stimulation of the intact ear . J Neurophysiol , 78 , 767 -779 . Mossop J.E. , Wilson M.J. , Caspary D.M. & Moore D.R . 2000 . Downregulation of inhibition following unilateral deafening . Hear Res , 147 , 183 -187 . Thai-Van H . 2013 . Unilateral deafness: A unique model for the investigation of functional plasticity mechanisms in the human auditory cortex . References Marriage JE , Moore BCJ , Stone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 217 publications
0
2
0
Order By: Relevance
“…Scale bar = 100 μm. Image taken from conference presentation, cited in published proceedings by Furness (2014).…”
Section: Fibrocytes As a Potential Target For Therapy In Hearing Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Scale bar = 100 μm. Image taken from conference presentation, cited in published proceedings by Furness (2014).…”
Section: Fibrocytes As a Potential Target For Therapy In Hearing Lossmentioning
confidence: 99%
“…Other substrates are also possible, and 3D culturing of fibrocytes is another way forward. Preliminary work in our lab (Furness, 2014) has shown that fibrocytes can be grown on a variety of substrates and 3D culturing of type III fibrocytes from guinea pig in hydrogels has been successful (Kelly et al, 2012). This paves the way for novel strategies to grow fibrocytes and use of an appropriate matrix that could direct the phenotypes of the cultured cells, even to potentially “bioprinting” a replacement ligament in vitro .…”
Section: Fibrocytes As a Potential Target For Therapy In Hearing Lossmentioning
confidence: 99%